Situational Fluidity and the Use of Identity Labels in Interactions - Andy Holmes; Amin Ghaziani (Socius)
The number of people who identify as LGBTQ+ more than doubled in the past decade, and with this growth has come an upsurge of expressive identity labels. However, that there are more labels available does not explain how people decide which to use. On the basis of 52 interviews, the authors show that LGBTQ+ people adopt multiple terms and adjust their usage relative to the interactional demands at hand. Inspired by research in psychology and population studies on sexual fluidity, the authors call the sociological variant situational fluidity . Two pathways motivate it. First, respondents anchor newer labels with established terms in the interest of smoother interpersonal interactions. Second, anticipating resistance encourages some individuals to alter their preferred labels in order to buffer against possible policing or pushback. This process-based account offers an alternative to traditional linear models that propose the achievement of a self that is articulated with a single and stable term.